Improving Detection of Prediabetes in Children and Adults: Using Combinations of Blood Glucose Tests - Okosun, Ike S.; Seale, J. Paul; Lyn, Rodney; Davis-Smith, Y. Monique (Frontiers in Public Health, 2015)
Highlights The combined use of fasting plasma glucose and hemoglobin A1c test is associated with significantly higher diagnostic rates of prediabetes across age, race/ethnicity, and BMI than using only one test. Combined use of fasting plasma glucose, hemoglobin A1c, and oral glucose tolerance test do not improve the overall and gender-specific prediabetes prevalence beyond what is observed using a combination fasting plasma glucose and hemoglobin A1c test. A redefined hemoglobin A1c test that incorporates racial/ethnic, gender, age, and BMI differences may provide a better way to use hemoglobin A1c test in population-based and clinical settings. Aim To determine combinations of blood glucose tests: oral glucose tolerance (OGT), fasting plasma glucose (FPG), and hemoglobin A1C (HbA1C) that are associated with highest diagnostic rates of prediabetes in non-diabetic American children and adults. Methods The 2007–2008 U.S. National Health and Nutrition Examination Surveys data were used for this study. Overall and specific prevalence of prediabetes (defined using OGT + FPG, OGT + HbA1C, HbA1C + FPG, and OGT + FPG + HbA1C tests) were determined across age, race/ethnicity, sex, and BMI categories. Results FPG + HbA1C test was associated with significantly higher diagnostic rates of prediabetes across age, race/ethnicity, and BMI. Estimates of overall prevalence of prediabetes using OGT + FPG, OGT + HbA1C, HbA1C + FPG, and OGT + FPG + HbA1C tests were 20.3, 24.2, 33, and 34.3%, respectively. Compared to OGT + FPG, the use of HbA1C + FPG test in screening was associated with 44.8, 135, 38.6, and 35.9% increased prevalence of prediabetes in non-Hispanic White, non-Hispanic Black, Mexican-American, and other racial/ethnic men, respectively. The corresponding values in women were 67.8, 140, 37.2, and 42.6%, respectively. Combined use of all blood glucose tests did not improve the overall and gender-specific prediabetes prevalence beyond what was observed using HbA1C + FPG test. Conclusion HbA1C criteria were associated with higher diagnosis rates of prediabetes than FPG and OGT tests in non-diabetic American children and adults. Using a combination of HbA1C and FPG test in screening for prediabetes reduces intrinsic systematic bias in using just HbA1C testing and offers the benefits of each test. A well-defined HbA1C that takes into consideration race/ethnicity, gender, age, and body mass index may improve detection of prediabetes in population and clinical settings.